2017
DOI: 10.1167/iovs.17-21589
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Design of Progressive Addition Lenses and the Lag of Accommodation in Myopes

Abstract: PURPOSE. Insufficient accommodative response is assumed to result in myopia progression. We have investigated if the accommodative lag in myopes is different between a single vision lens (SVL) and the progressive addition lens PAL 2, clinically trialled for its ability to reduce progression of myopia, and if there exist differences in accommodative lag between PAL 2 and other PALs with the same addition power (þ1.50 D).METHODS. The influence of spherical SVL and four different designs of PALs that differ in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 29 publications
(29 reference statements)
0
21
0
2
Order By: Relevance
“…Since the near addition zones induce localised superior relative peripheral retinal myopic defocus, and the relative superior peripheral refractive shift was found to be associated with a reduction in the rate of central myopic refractive progression of a one‐year period in progressive addition lens wearers, this may be a possible alternative mechanism by which these lenses slow myopia progression . Progressive addition and bifocal spectacle lenses will vary the optics of the eye as a result of a change in accommodation response from the near addition as well as the variable optics in the periphery of the lenses.…”
Section: Hoas and Myopia Control Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the near addition zones induce localised superior relative peripheral retinal myopic defocus, and the relative superior peripheral refractive shift was found to be associated with a reduction in the rate of central myopic refractive progression of a one‐year period in progressive addition lens wearers, this may be a possible alternative mechanism by which these lenses slow myopia progression . Progressive addition and bifocal spectacle lenses will vary the optics of the eye as a result of a change in accommodation response from the near addition as well as the variable optics in the periphery of the lenses.…”
Section: Hoas and Myopia Control Interventionsmentioning
confidence: 99%
“…Figure and data adapted from Buehren et al 123,135,141 wearers, this may be a possible alternative mechanism by which these lenses slow myopia progression. 163 Progressive addition and bifocal spectacle lenses will vary the optics of the eye as a result of a change in accommodation response from the near addition 161,164 as well as the variable optics in the periphery of the lenses.…”
Section: Spectacle Lenses: Bifocal and Progressive Addition Lensesmentioning
confidence: 99%
“…The present study also highlighted the abnormal accommodative response of patients with TBI to five different stimulus levels. Normally, when viewing near targets, people under 40 years of age manifest a mild amount of accommodative lag 2017. However, with the accommodative stimulus increased, the TBI group presented more lag.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, when viewing near targets, people under 40 years of age manifest a mild amount of accommodative lag. 37 However, with the accommodative stimulus increased, the TBI group presented more lag. We speculate that this was predominantly a consequence of accommodative fatigue.…”
Section: Table 2 Comparison Of Accommodation Function Values Betweenmentioning
confidence: 98%
“…Thus, the near addition selected for a particular study may not be suitable for some of the recruited children . Additionally, it has been recently shown that not only the amount of addition but the distribution of optical power through the near vision zone of PALs can also influence accommodative responses …”
Section: Optical Strategies Of Myopia Controlmentioning
confidence: 99%